Organizações da sociedade civil da Guiné-Bissau: debatendo o seu papel no desenvolvimento das comunidades locais do país - Baldé, Bacar (2023)
The current Guinean political scenario invites us to resume a debate on democracy and the role that civil society plays in the country. The work sought to analyze the current context through an interdisciplinary descriptive study addressing the current situation in the country and the successive coups d'état as obstacles to socioeconomic and political-institutional development. With the main focus on debating the role of Guinean civil society. I seek to frame this theme through the discussion of the main “classical” theories about the modern State, Democracy and Civil Society, confronted with the theoretical contribution of some contemporary authors. From the debate involved in these theories, analyzes were made based on the Guinean reality itself. These analyzes allowed us to arrive at certain considerations about the progress of both democracy and civil society and its relationship with the State in Guinea-Bissau. After analyzing the current political situation and confronting theorists who have already addressed similar issues at different times, it was noticed that Guinean civil society does not only cover formal entities of organized interest groups, but also a wide variety of traditional forms of social cooperation in the different ethnic communities existing in the country. It is considered that it would be possible and desirable for the Guinean state to promote the appreciation and eventual adaptation of conflict resolution practices of some ethnic groups (Balanta and Mandinga) to mobilize and engage these communities in local development projects. Finally, it was also concluded that the still precarious and unstable character of democracy in Guinea-Bissau limits the performance of CSOs, removing the possibility that they can achieve their objectives and implement their projects, usually interrupted when a coup occurs or if overthrow a government.